Etika Kegiatan Produksi: Perspektif Etika Bisnis Islam - Ahmad Suminto (Islamic Economics Journal, 2020)
In principle, production activities are bound to the level of Islamic moral and technical values, especially on the quality aspects of products. The values cover all activities during organizing production factors, choosing materials for production, production processes, quality assurance (quality), marketing, service and customer care. This guidance is not only for obeying the commands and prohibitions of Allah and His Messenger but also improving a better understanding throughout practising these moral values. This research uses a library research method with a descriptive-analytic qualitative approach, which explains and illustrates the object of research and then analyses it from the perspective of business ethics in Islam. The analysis technique is the content analysis method which contains the methods of induction, deduction, and comparison. This study aims to uncover the Ethics of Production in Islam: Perspective of Islamic Business Ethics with various case studies and information on events that the author gets. The results show that Muslim producers should consider two principles as an ethical foundation in production activities and to be in harmony with maqasid shariah. First: producing in halal circles, Islam firmly classifies goods (sil’ah) or commodities into two categories. The goods are called al-Qur’an with tayyibat, i.e. goods that are legally halal consumed and produced. Khaba'ith, i.e. goods that are legally haram consumed and produced. Second, the protection of natural resources without damaging the environment.